Combined effects of local curvature and elasticity of an isothermal wall for jet impingement cooling under magnetic field effects - Selimefendigil, Fatih; Cogan, Mehmet; Öztop, Hakan Fehmi (Journal of Central South Univ, 2021)
The aim of this study is to examine the effects of local curvature and elastic wall effects of an isothermal hot wall for the purpose of jet impingement cooling performance. Finite element method was used with ALE. Different important parametric effects such as Re number (between 100 and 700), Ha number (between 0 and 20), elasticity (between 10(4) and 10(9)), curvature of the surface (elliptic, radius ratio between 1 and 0.25) and nanoparticle volume fraction (between 0 and 0.05) on the cooling performance were investigated numerically. The results showed that the average Nu number enhances for higher Hartmann number, higher values of elastic modulus of partly flexible wall and higher nanoparticle volume fraction. When the magnetic field is imposed at the highest strength, there is an increase of 3.85% in the average Nu for the curved elastic wall whereas it is 89.22% for the hot part above it, which is due to the vortex suppression effects. Nanoparticle inclusion in the base fluid improves the heat transfer rate by about 27.6% in the absence of magnetic field whereas it is 20.5% under the effects of magnetic field at Ha=20. Curvature effects become important for higher Re numbers and at Re=700, there is 14.11% variation in the average Nu between the cases with the lowest and highest radius ratio. The elastic wall effects on the heat transfer are reduced with the increased curvature of the bottom wall.
Keywords: jet impingement; nanoparticles; elastic wall; MHD; CFD; curved wall